Borrowing Agreement with the Government of the United Kingdom. (Policy Papers; Policy Paper, 2009)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, the Government of the United Kingdom, acting through Her Majesty's Treasury, agrees to lend to the Fund up to the equivalent of SDR 9.92 billion.